A case report: The third-largest case in the literature of a vulvar lipoma - Gokmen Sukgen (Wolters Kluwer Medknow Publications, 2020)
Lipoma is the most common soft-tissue tumor of mesenchymal tissue origin although very rarely found in the vulva. The present study aims to present a very rare and big lipoma. In this case, the patient was 70 years old and was admitted to our clinic with the complaint of soft vulvar mass, 17 cm × 14 cm × 10 cm in size. The mass appeared about 7 years ago and was growing for the past 2 years and extended to the labium majus from the left inguinal region. The author performed a vulvar reconstruction with total excision of the mass. Pathological examination revealed a lipoma. Vulvar lipoma should be considered in the differential diagnosis of vulvar masses, although lipomatous masses are rarely seen in vulva.